TiOx-supported Na-Mn-W oxides for the oxidative coupling of methane - Aireddy, Divakar R.; Roy, Amitava; Cullen, David A.; Ding, Kunlun (Catalysis today, 2023)
Supported Na-Mn-W oxides are among the most studied catalysts for the oxidative coupling of methane (OCM) because of their superior thermal stability and relatively high C2+ product yields. However, because of the structural complexity, the roles of each component in these catalysts have been controversial. In this work, WOx and MnOx sites were supported on titanate nanowires and employed in OCM studies. Compared to the commonly studied silica support, which is subject to severe restructuring due to the Na-induced crystallization, titanate support not only serves as a reservoir for alkali metals (e.g., Na), but also stabilizes isolated MnOx species. The catalytic performance of the titanate-based catalyst is similar to that of reference catalyst, MnOx/Na2WO4/SiO2, with a synergistic effect between MnOx and WOx sites. Advanced electron microscopy, X-ray diffraction, infrared spectroscopy, and X-ray absorption near edge structure spectroscopy suggest that the basic NaOx and MnOx species have strong interactions with the acidic WOx and TiOx species, which might contribute to the high selectivity toward C2+ products and suppressed COx formation. [Display omitted] •Titanate-supported Na-Mn-W oxides show comparable performance with MnOx/Na2WO4/SiO2 in the oxidative coupling of methane.•Mn is isolated and stabilized as Na2Mn2Ti6O16.•W is present as Na2WO4 phase and enriched on the surface of the catalyst.•MnOx and WOx species show synergistic effects in the oxidative coupling of methane.